The Spiritual Dimension of Teacher Professionalism: An Analysis of the Hadith on Seeking Knowledge and Its Relevance for Contemporary Islamic Education - Nabilla Resti Aprilia; Sarwadi Sulisno (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
This conceptual article stems from concerns about the multidimensional challenges facing Islamic education in the contemporary era, such as digitalization, quality gaps, and the crisis of curriculum relevance. Using a qualitative literature study method, this research conducts an in-depth investigation to answer the main question: are classical theological foundations, particularly hadiths on seeking knowledge, still relevant in addressing the challenges of today? The research findings reveal that theological principles in the hadith, such as the obligation to seek knowledge (farḍ), its orientation as a path to paradise, and the criteria for its usefulness, contain dynamic values that can serve as an ethical and philosophical compass. These values are not outdated but rather offer a solution-oriented framework for designing an Islamic education that is adaptive, integrative, and character-based. Furthermore, this research shows that the internalization of these values has a direct impact on increasing students' intrinsic learning motivation and shaping the professional framework of teachers who are not only techno-pedagogically skilled but also spiritually strong. Thus, this article concludes that revitalizing understanding of theological foundations is not merely a matter of preserving heritage, but rather a strategic imperative for establishing an Islamic education that is authentic, superior, and responsive to global change.